Islamic radicalism in the problems of international terrorism: the issue of national security (International relations and international law Journal, 2016)
The article is devoted to one of the most pressing problems of the world community the problem of international terrorism as a threat to national security. International terrorism in the context of globalization has the typical features and peculiarities of «Islamic radicalism.» New terrorist organization «Islamic State of Iraq and the Levant» and the radical organization «Boko Haram» are defined as «atypical» for international terrorism. Experts predict the expansion of the sphere of influence of the Islamic state and the spread of his ideas. This is cause for concern in the countries of Central Asia. The military operations of the IG involved many citizens of post-Soviet states. International terrorism has become a tool to achieve political goals of interest groups. Actualized the problem of Islamic radicalism poses a threat for Kazakhstan. Considered the normative aspect of the international participation of Kazakhstan in combating terrorism.
Keywords: international terrorism; Islamic radicalism; Islamic State of Iraq and the Levant; the Law on National Security of Kazakhstan